1997
DOI: 10.1038/sj.bjp.0701271
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of the effects of the antitumour ether lipid ET‐18‐OCH3 on cytosolic calcium and on apoptosis

Abstract: 1 We have compared the e ects of 1-O-octadecyl-2-O-methyl-sn-glycero-3-phosphocholine (ET-18-OCH 3 ) on the cytosolic free calcium concentration ([Ca 2+ ] i ) and on apoptosis in several normal and leukaemia cells, including human polymorphonuclear neutrophils (PMNs), U937 cells, and undi erentiated as well as dimethylsulphoxide-di erentiated HL60 cells (uHL60 and dHL60, respectively). 2 ET-18-OCH 3 produced apoptosis, as evidenced by DNA degradation into oligonucleosome-size fragments, in U937 and uHL60 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Edelfosine (10 µM) was unable to induce apoptosis in J774 cells following 24 h incubation (<2% apoptosis), and caused less than 15% apoptosis after 48 h incubation. This is in stark contrast to the high sensitivity of other monocyte-like cell lines to edelfosine, such as human U937 cells [28] , [55] , [56] , which undergo rapid apoptosis and can therefore not be used as host cells to analyze the effect of ALPs on intracellular parasites residing in macrophages. Incubation of J774 macrophages with PTE-ET showed that the fluorescent edelfosine analog was taken up into the cell ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 92%
“…Edelfosine (10 µM) was unable to induce apoptosis in J774 cells following 24 h incubation (<2% apoptosis), and caused less than 15% apoptosis after 48 h incubation. This is in stark contrast to the high sensitivity of other monocyte-like cell lines to edelfosine, such as human U937 cells [28] , [55] , [56] , which undergo rapid apoptosis and can therefore not be used as host cells to analyze the effect of ALPs on intracellular parasites residing in macrophages. Incubation of J774 macrophages with PTE-ET showed that the fluorescent edelfosine analog was taken up into the cell ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 92%
“…It must be noted that edelfosine, 2-APB and tetracaine are not entirely selective for their targets. Thus, edelfosine, in addition to inhibiting PLC, also activates platelet-activating factor (PAF) receptors [ 48 ]. While 2-APB inhibits the IP 3 Rs without an effect on the RyRs [ 49 ], it also inhibits TRPC3, 6 and 7 channels in VSMCs [ 50 ].…”
Section: Resultsmentioning
confidence: 99%